Mobile applications and internet banking for Greek enterprises - Challoumis, Constantinos; Eriotis, Nikolaos; Vasiliou, Dimitrios (Edelweiss Applied Science and Technology, 2025)
This paper examines how mobile applications, when tightly integrated with Internet banking, can accelerate the digital transformation of Greek enterprises. It synthesizes the technology stack (UI modules, data management, gateways, messaging, and security), regulatory context, user experience determinants, and market dynamics, and complements these with case-style insights and a brief EU comparison. Findings indicate that, although online and mobile banking penetration in Greece has lagged behind EU averages, mobile access is now the primary driver of uptake. The integration imperative—shared services/APIs over reliable back-ends—emerges as the central technical enabler, while perceived security (confidentiality, strong authentication, non-repudiation) remains the dominant adoption barrier. User experience quality and multichannel consistency strongly influence usage frequency and trust, and legacy infrastructure plus skills gaps constrain delivery speed. The trajectory points to the convergence of mobile and web banking, with branches shifting toward advisory roles. Practical recommendations include a mobile-led product roadmap, investment in resilience and observability of back-end services, rigorous multi-factor authentication (MFA)/device binding and risk controls, a unified design system across channels, and analytics-driven customer relationship management (CRM) for personalization. Overall, the paper offers an end-to-end view connecting technology, regulation, and strategy to guide executives and practitioners in scaling secure, user-centric mobile banking within Greece’s banking ecosystem.